HIV and sexually transmitted infections at the borderlands: situational analysis of sexual health in the Brazilian Amazon. Issue 4 (7th February 2012) - Benzaken, Adele; Sabidó, Meritxell; Galban, Enrique; Rodrigues Dutra, Daniel Lúcio; Leturiondo, André Luiz; Mayaud, Philippe
Abstract : Objectives: The borderlands are considered areas of increased vulnerability to HIV and sexually transmitted infections (STI). The study aimed to determine the STI/HIV prevalence and risk factors in the triple-border area of the Brazilian Amazon. Methods: A situational analysis of sexual health was conducted in three cities of the Alto Solimões region. This multicomponent research approach included key informant interviews, participant observations and mapping of places where people meet sexual partners. Volunteers recruited from the 'hot spots' in each city were invited for interview and STI/HIV testing. Results: Over 6 months, 598 participants were recruited, 285 men of median age 28 years (IQR, 23–37) and 313 women of median age 29 years (IQR, 24–37). Overall, 49.3% reported a casual partner during the past 3 months, but only 38.5% reported consistent condom use. The respective prevalences in men and women were Neisseria gonorrhoeae (1.1% and 0.3%), Chlamydia trachomatis (1.4% and 4.8%), high-risk human papillomavirus (14.4% and 24.0%), active syphilis (3.2% and 2.6%), herpes simplex virus type-2 (51.1% and 72.1%), hepatitis B virus (by hepatitis B virus surface antigen) (7.5% and 4.6%), hepatitis C virus (0.7% and 0.7%) and HIV (1.4% and 0.0%). Risk factors for viral STIs included female sex and age. Conclusions: While the main conditions that contribute to the spread of HIV are in place in the triple-border area, the prevalence of bacterial STIs and HIV are still relatively low, providing a window of opportunity for interventions.